The Effect of Next Profit Margin, Price to Book Value and Debt to Equity Ratio to stock Return in the Indonesian Consumer Goods Sector - Dita, Amalia Husna; Murtaqi, Isrochmani (Journal of Business and Management, 2014)
In the recent years, stocks have become one of the most chosen investments in Indonesia. One of the most interesting sectors for investors is the consumer goods sector, for this sector managed to survive during the crisis and negative sentiments in Indonesian stocks market. Having the fact that the consumer goods sector is promising, investors would like to know the return of shares in this sector. One of the parameter that can be used to project the stock return is ratio from financial statement. This research is conducted to find out the relationship between net profit margin, price to book value, and debt-equity ratios with stocks return in the Indonesian consumer goods industry. The samples in this research are the consumer goods companies listed in Indonesia Stock Exchange during the period of 2009 – 2013. The multiple linear regression analysis is chosen as the method to analyze it. Results shown that the net profit margin, price to book value, and debt equity ratio have significant effects towards stocks return. Two of them, which are net profit margin and debt equity ratio have the positive significant impacts to the stocks return, while the price to book value has a significantly negative relationship to stocks return. Results also show that the R-square of the variable values 54.9%. NPM gives the most significant influence to the stocks return, followed by the PBV, and the last one is the DER.Keywords: Net profit margin, price to book value, debt to equity, stock return, multiple linear regression.